Reciclado de bioresiduos para producción de larvas de Mosca doméstica - Baño Guanotuña, Víctor Robinson (2018)
The study biowaste recycling for the production of housefly larvae was performed in the canton Píllaro province of Tungurahua. this tool is viewed as an important part to reduce the environmental effect of the organic poultry companies excretion and dead birds they generate. He raised the bioreciclador to design a living protein production, for which the biowaste produced by local poultry were characterized, a functional bíoreciclador was designed and functional biowaste recycling unit is a prototype. biowaste poultry study were characterized, residence times and volumes were determined biowaste were determined to be recycled. With this information biorecicladores were sized, creating a design and unit functions suitable for the local environment. The digital modeling of bioreciclador was performed in SketchUp (2017) 3D software. The digital pattern comprises a rectangle of 0.97 meters in length are divided into three parts including two 0.20 meters and 0.57 meters last with a width of 0.30 meters. Bioreciclador implementation, allows to process 12 kg of biowaste, 9 function for recycling of 103.53 kg of biowaste daily units produced by the poultry being necessary. The prototype is planned to make an alternative, being accurate, easy to implement in the field of moderate cost, satisfying the needs of research for the production of larvae.